The Influence of Academic Self-Efficacy and Self-Esteem on Academic Achievement: A Study on Accounting Students - Sari, Maria Mediatrix Ratna; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 32 No 3 (2022), 2022)
The purpose of this study was to determine the impact of academic self-efficacy and self-esteem on accounting students' academic achievement at Faculty of Economics and Business, Udayana University. In this study, linear regression analysis was used as an analytical technique. The sample for this study is bachelor accounting students from the class of 2016, and the sample was determined using the Slovin formula, which yielded 77 people. The data was analysed using multiple linear regression. The findings indicated that good academic self-efficacy can improve accounting students' academic achievement. Similarly, rising self-esteem boosts academic achievement among accounting students at Faculty of Economics and Business, Udayana University. This study is also expected to provide an overview of accounting students' academic self-efficacy in order to determine future attention steps in the learning process, which can shape the character of the nation's children who are superior, independent, and cultured. Keywords: Academic Self-Efficacy; Self-Esteem; Academic Achievement; Student’s GPA.